Dynamic study of Xi ’an’s high-quality development status - Xu, Qinghai (International Journal of Global Economics and Management, 2024)
According to the connotation of high-quality development, this paper takes Shaanxi Province as the research object, establishes a high-quality development level model, selects 24 indicators to establish an indicator system, assigns them by entropy weight method, and evaluates the high-quality development status of Xi ’an from 2012 to 2021 by combining TOPSIS method. The results show that the high-quality development of Xi ’an city has developed from a low level to a high level from 2012 to 2021, and the development trend is good. During the study period, the innovation, coordination, green, opening and sharing indexes of Xi ’an City show a gradually rising trend. The research shows that the high-quality development of Xi ’an city has made some progress, but some indicators can be further optimized, which has reference significance for the economic development of Xi ’an city.